High-Performance and Fabrication-Tolerant 3 dB Adiabatic Coupler Based on Ultralow-Loss Silicon Waveguide by Tri-Layer Hard Mask Etching Process - Ke Zhang; Yunchu Yu; Nanfei Zhu; Senlin Zhang; Jie Sun; Shijin Ding; David Wei Zhang (Nanomaterials, 2025)
Silicon photonics has emerged as critical for advancing photonic integrated circuits (PICs), but waveguide losses, primarily resulting from sidewall roughness, remain a primary challenge. In this work, we demonstrate a tri-layer hard mask etching process that produces strip silicon waveguides with propagation losses as low as 1.48 dB/cm, i.e., a 37% improvement over the conventional Si3N4 hard mask technique. Based on the abovementioned approach, the fabricated 3 dB adiabatic directional couplers achieve a nearly ideal splitting ratio of 50.2:49.8 as well as an excess loss of 0.067 dB. These results indicate that the tri-layer hard mask etching process enables scalable and ultralow-loss PICs to be fabricated for high-speed optical interconnects and quantum computing systems.